2002
DOI: 10.1039/b206473a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized hyperbranched grafts on polyethylene powder for support of Pd(0)-phosphine catalyst

Abstract: Hyperbranched grafts of poly(acrylic acid) have been modified with phosphine ligands for support of Pd(0) for use in allylic substitution chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Such an observation has been previously reported for a copper catalyst grafted on SBA‐15 silica and used in epoxidation reactions,78 or Ti‐MCM‐41 catalyst applied in oxidative desulfurization79 and epoxidation 80. Unfortunately, from these results, it seems that the surface hydrophobization also prevents redeposition of leached species as was already observed in some polymeric materials bearing Pd complexes and used in cross‐coupling reactions 81,82. These results are in agreement with what was observed during the catalytic run while using Pd(PPh 2 ) 2 @SBA‐3 catalyst whose surface had been silylated with TMSCl prior to surfactant removal (Table 2) when considering the longer reaction time for the latter and the reduced redeposition capacity.…”
Section: Resultssupporting
confidence: 69%
“…Such an observation has been previously reported for a copper catalyst grafted on SBA‐15 silica and used in epoxidation reactions,78 or Ti‐MCM‐41 catalyst applied in oxidative desulfurization79 and epoxidation 80. Unfortunately, from these results, it seems that the surface hydrophobization also prevents redeposition of leached species as was already observed in some polymeric materials bearing Pd complexes and used in cross‐coupling reactions 81,82. These results are in agreement with what was observed during the catalytic run while using Pd(PPh 2 ) 2 @SBA‐3 catalyst whose surface had been silylated with TMSCl prior to surfactant removal (Table 2) when considering the longer reaction time for the latter and the reduced redeposition capacity.…”
Section: Resultssupporting
confidence: 69%
“…First, XPS analysis of Pd crystallites in a hyperbranched graft of Pd-PE-g-PAA showed a Pd 3d 3/2 peak at 333.3 eV. This peak was discernibly different than the peak for a previously described immobilized molecular catalyst -a Pd(0) complex prepared using the same polymer that had been further modified to contain aminodiphenylphosphinopropyl ligands (i.e., Pd(0)-DPPA-PE-g-PAA; DPPA is diphenylphosphinopropylamide containing a phosphine ligand that was covalently coupled to poly(acrylic acid)-grafted PE via an amide bond) (25). No evidence was obtained for the presence of phosphine in the recovered PE support after a reaction, suggesting that added phosphine was not sorbed into the resin.…”
Section: Resultsmentioning
confidence: 82%
“…2% to 3% Pd leaching was seen in the reaction between allyl acetate and diethylamine with external phosphine. Pd leaching was not seen with Pd(0)-DPPA-PE-g-PAA catalysts that contained covalently bound phosphine ligands within the functional polymer support that formed analogs of a molecular Pd(0) catalyst (25). Taken together, these results are consistent with an explanation such as that proposed previously (3) for the activity of these Pd-PE-g-PAA colloidal catalysts, which is based on leaching of a phosphine-ligated Pd catalyst or a Pd cluster.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The authors found a correlation between the nature and character of the complex used in the polymer matrix particles of palladium. It was shown that the higher the lipophilicity of compounds of palladium, the greater the amount of metal possible to introduce into the polymer matrix and for the most lipophilic compounds is not observed the formation of particulate metal, and continuous layers covering the internal void in the structure of the polymer matrix 3,6. Using (PhCN) 2 PdCl 2 and (CH 3 CN) 2 PdCl 2 not lead to optimal results, as lipophilicity acetonitrile complex appeared excessive and benzonitrile complex in sufficient [6][7][8] . Based on these data, it was assumed that an optimum combination of properties, including lipophilicity and the decomposition temperature is necessary to use a palladium complex, wherein the ligand is used as the fatty-aromatic nitrile having in the molecule both an aromatic moiety and aliphatic.…”
Section: Introductionmentioning
confidence: 99%